Neutrophil–lymphocyte ratio predicts overall and recurrence‐free survival after liver transplantation for hepatocellular carcinoma. Issue 7 (30th November 2012) - Limaye, Alpna R.; Clark, Virginia; Soldevila‐Pico, Consuelo; Morelli, Giuseppe; Suman, Amitabh; Firpi, Roberto; Nelson, David R.; Cabrera, Roniel
<x xml:space="preserve">Abstract</x> Aim The goal of this study is to evaluate whether an elevated neutrophil–lymphocyte ratio (NLR) at the time of diagnosis predicts survival of patients with hepatocellular carcinoma (HCC) after liver transplantation (LT). We hypothesize that the NLR is predictive of overall survival (OS) and recurrence‐free survival (RFS) in patients with HCC who undergo LT. Methods This is a retrospective analysis of adult patients undergoing LT for HCC between 2000 and 2008 at our institution. We define an elevated NLR as a ratio of 5 or greater. Results We included 160 patients who underwent LT for HCC in the time period, of whom 28 had an elevated NLR. Seventeen subjects experienced recurrent HCC during the study period. The cumulative survival among subjects with an elevated NLR was significantly lower than among subjects with a normal NLR. On univariate analysis, several factors (including an elevated NLR) predicted decreased OS and RFS. However, after multivariate analysis, only three factors (including elevated NLR) remained significant as predictors of OS. Additionally, multivariate analysis revealed that an elevated NLR was the only significant independent predictor of RFS. Conclusion Preoperative NLR is a powerful independent predictor of OS and RFS in patients undergoing LT for HCC. Measurement of NLR could serve as a useful and easily obtained adjunct to the Model for End‐Stage Liver Disease score and Milan criteria when evaluating this patient population and determining which patients will gain the most survival benefit from transplantation.